Sistem Monitoring Jarak Jauh Pada Peternakan Kandang Ayam Petelur Terintegrasi Telegram - Wicaksono, Mahasadaru; Fatkhurrozi, Bagus; Setiawan, Hery Teguh (CV. Ulil Albab Corp, 2024)
If the ammonia gas level exceeds the threshold of 25 PPM, it affects the mucous membranes of the eyes, respiratory tract, propagation of disease agents, immune system, and the reproductive system of livestock. The solution involves monitoring the level of ammonia gas on layer chicken farms to minimize air pollution, ensuring the undisturbed growth of layer chickens. This research employs IoT to monitor the level of ammonia gas on layer chicken farms without distance limitations. The MQ-137 ammonia sensor can read values ranging from 8-50 PPM. The largest error value is 10%, with an average error of 4%. The system is considered successful when the sensor consistently provides accurate readings. When applied to chicken farm enclosures, the highest ammonia value obtained is 5.95 PPM. Notifications work effectively in case of ammonia levels exceeding or falling below the threshold, and during rainy or dry conditions. The system sends notifications three times with a one-minute delay. Upon receiving notifications, a button appears to request turning on or off the fan. The device can send notifications and control the fan regardless of distance, as long as the device and Telegram are connected to the internet.